2015
DOI: 10.3390/met5020850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indium Content on the Microstructure, Mechanical Properties and Corrosion Behavior of Titanium Alloys

Abstract: Ti-xIn (x = 0, 5, 10, 15 and 20 wt%) alloys were prepared to investigate the effect of indium on the microstructure, mechanical properties, and corrosion behavior of titanium with the aim of understanding the relationship between phase/microstructure and various properties of Ti-xIn alloys. The Ti-xIn alloys exhibited a lamellar α-Ti structure at an indium content of up to 20 wt%. High-resolution TEM images of the Ti-xIn alloys revealed that all the systems contained a fine, acicular martensitic phase, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Han et al [ 79 ] has further studied the corrosion behaviour, mechanical properties and microstructures of Ti-In binary alloys, which confirm with another study by Wang et al [ 78 ] that the strength and microhardness of the alloys were increased. Furthermore, in the experimental Ti–In alloys and cp-Ti in Wang [ 78 ] showed a good and similar cytocompatibility.…”
Section: Binary Titanium Alloyssupporting
confidence: 61%
See 1 more Smart Citation
“…Han et al [ 79 ] has further studied the corrosion behaviour, mechanical properties and microstructures of Ti-In binary alloys, which confirm with another study by Wang et al [ 78 ] that the strength and microhardness of the alloys were increased. Furthermore, in the experimental Ti–In alloys and cp-Ti in Wang [ 78 ] showed a good and similar cytocompatibility.…”
Section: Binary Titanium Alloyssupporting
confidence: 61%
“…Furthermore, Ti–10In and Ti–15In (10 and 15 denote the respective Indium wt%) showed a transpassive behaviour and lower current densities at high potentials under the presence of NaF. Han et al [ 79 ] has shown Ti-In alloys (5–20 wt% In) not only exhibit a similar corrosion resistance to cp-Ti by electrochemistry, but even a superior oxidation resistance compared to cp-Ti was revealed in Ti-In alloys. Therefore, Ti-In alloys might give a good or better corrosion resistance as cp-Ti.…”
Section: Binary Titanium Alloysmentioning
confidence: 99%
“…There have been some studies reported on binary alloys of indium with titanium [89,90]. Like zirconium, indium has also been used in multi-component alloys, such as Ti-In-Nb-Ta, where the alloy showed good bioactivity [91].…”
Section: Binary Alloys Of Titaniummentioning
confidence: 99%
“…Like zirconium, indium has also been used in multi-component alloys, such as Ti-In-Nb-Ta, where the alloy showed good bioactivity [91]. In binary alloys, indium imparted increased strength and also corrosion resistance that was at least as good as cpTi [90]. This, in turn, led to the alloy having good biocompatibility in cell cultures.…”
Section: Binary Alloys Of Titaniummentioning
confidence: 99%
“…The remaining three papers are more application focussed with the work by Kotte [11] addressing the requirement for titanium alloys to be used as joining parts to light weight materials, such as aluminium and fibre reinforced plastics in the aerospace industry, whereas the work by Han [12] and a review paper by Petersen [13] relate to critical requirements in medical-based applications. Both papers are informative regarding the use of titanium alloys for orthopaedic and dental implant applications, featuring up to date issues and offering potential future solutions.…”
Section: Open Accessmentioning
confidence: 99%